2021
DOI: 10.3934/publichealth.2021008
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status and cardiovascular risk profile in Cameroonian military population

Abstract: Background Periodontal diseases (PD) seem to appear today as predictors of some cardiovascular diseases (CVD). There is a lack of data on the oral health among Cameroonian military population, and its relationship with CVD. Purpose Investigate on the link between oral health of Cameroonian military from the Ngaoundéré garrison and their cardiovascular risk profile. Participants and methods A cross-sectional study at the Fifth Military Sector … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
0
0
Order By: Relevance
“…They also confirmed tobacco smoking being a common risk factor for periodontitis and CVDs (odds ratio: 4.44 [1. 73-11.43], p = 0.0031), and indicated that poor oral hygiene, which is a well-known risk factor for periodontitis, also increases the risk of CVDs [82].…”
Section: Oral Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…They also confirmed tobacco smoking being a common risk factor for periodontitis and CVDs (odds ratio: 4.44 [1. 73-11.43], p = 0.0031), and indicated that poor oral hygiene, which is a well-known risk factor for periodontitis, also increases the risk of CVDs [82].…”
Section: Oral Healthmentioning
confidence: 99%
“…Increased oxidative stress through generation of ROS, endothelial dysfunction, oxidation of both HDL and LDL, reverse cholesterol transport, elevated plasma fibrinogen levels and inflammatory marker levels (C-reactive protein (CRP) and interleukin-6 (IL-6), increase in the inflammatory process, changes in the thrombosis/fibrinolysis system, hypercholesterolemia, decreased HDL levels, increased blood pressure, increased blood tendency to clotting, increased heart rate, enhanced excretion of thromboxane, which results in increased vasoconstrictive properties of smoking, increased sympathetic activities and plasma catecholamine levels, elevated plasma noradrenaline levels, increased resting heart rate and decreased heart rate variability, higher total cholesterol levels [9,70,72,74,80] Oral health Production of inflammatory mediators such as tumor necrosis factor α (TNF-α), interleukins (IL-1, IL-6, IL-8), and CRP, presence of Porphyromonas gingivalis, Aggregatibacter actinomycetemcomitans, and Streptococcus sanguis in patches of atheroma [82]…”
Section: Stressmentioning
confidence: 99%